Guide to the essentials in emergency medicine - Ooi, Shirley; Manning, Peter
This book focuses on the practical management of the most life-threatening and common conditions encounterd by emergency physicians. It is designed to offer a balanced viewpoint advocating the tenets of evidence-based medicine